Açaí (Euterpe oleracea Mart.) presents anti-neuroinflammatory capacity in LPS-activated microglia cells. (3rd June 2022) - de Souza, Diulie Valente; Pappis, Lauren; Bandeira, Thuany Teixeira; Sangoi, Gabriela Geraldo; Fontana, Tuyla; Rissi, Vitor Braga; Sagrillo, Michele Rorato; Duarte, Marta Maria; Duarte, Thiago; Bodenstein, David Frederick; Andreazza, Ana Cristina; Cruz, Ivana Beatrice Mânica da; et al.
ABSTRACT: Introduction: Neuropsychiatric diseases are responsible for one of the highest burden of morbidity and mortality worldwide. These illnesses include schizophrenia, bipolar disorder, and major depression. Individuals affected by these diseases may present mitochondrial dysfunction and oxidative stress. Additionally, patients also have increased peripheral and neural chronic inflammation. The Brazilian fruit, açaí, has been demonstrated to be a neuroprotective agent through its recovery of mitochondrial complex I activity. This extract has previously shown anti-inflammatory effects in inflammatory cells. However, there is a lack of understanding of potential anti-neuroinflammatory mechanisms, such as cell cycle involvement. Objective: The objective of this study is to evaluate the anti-neuroinflammatory potential of an açaí extract in lipopolysaccharide-activated BV-2 microglia cells. Methods: Açaí extract was produced and characterized through high performance liquid chromatography. Following açaí extraction and characterization, BV-2 microglia cells were activated with LPS and a dose-response curve was generated to select the most effective açaí dose to reduce cellular proliferation. This dose was then used to assess reactive oxygen species (ROS) production, double-strand DNA release, cell cycle modulation, and cytokine and caspase protein expression. Results: Characterization of the açaí extract revealed 10 bioactive molecules. The extract reduced cellular proliferation, ROS production, and reduced pro-inflammatory cytokines and caspase 1 protein expression under 1 μg/mL in LPS-activated BV-2 microglia cells but had no effect on double strand DNA release. Additionally, açaí treatment caused cell cycle arrest, specifically within synthesis and G2/Mitosis phases. Conclusion: These results suggest that the freeze-dried hydroalcoholic açaí extract presents high anti-neuroinflammatory potential.